Learning the Koto - Halliwell, Patrick (Canadian University Music Review / Revue de musique des universités canadiennes, 1994)
This paper examines traditionally-oriented teaching and learning processes in Japanese koto music. Earlier evaluations (negative and positive) by Western scholars are introduced, together with a brief comparison to Western practices. A distinction is made between "inside" and "outside" students; the former have greater exposure to music and speech about music, and teaching methods also may differ. Traditional methods of learning through imitation are shown to have other musical goals besides the transmission of musical "text." Playing together is fundamental; teachers may use speech, shôga (oral representation of instrumental sound), or purely musical means to convey information to the student. Notation, often used nowadays, is nevertheless of relatively minor importance. The dominant values underlying traditional teaching methods are expressed through the phrase "if you can steal it, that's OK." Finally, concepts of "text" and "interpretation" are considered in relation to values concerning change in traditional koto music.